Engineering glucose oxidase for bioelectrochemical applications - Mano, Nicolas (Bioelectrochemistry (Amsterdam, Netherlands), 2019)
There is still a growing interest in developing glucose sensors using glucose oxidase. Since 2012, over 1000 papers are published every year, while efficient commercial sensors exist on the market. Among those glucose sensors, few have been thought and well-engineered and do not solve the problems associated with glucose oxidase; among which the O sensitivity of the enzyme or the competition between O and redox mediators for GOx's electrons. Enzyme engineering has been employed to solve those issues but screening GOx in homogeneous solution with O as an electron acceptor is not suitable. Very few reports describe the specific reengineering of GOx for electrochemical applications and are the subject of this review. It starts with a brief presentation of glucose oxidase and presents the recent progress in glucose oxidase reengineering by highlighting the kind of engineering/mutations performed to increase its electron transfer rate to electrode surfaces and, to decrease its O sensitivity. In addition, the review highlights the need to develop new screening methods involving electrochemical probing, essential to develop the next generation of glucose sensors; specific to glucose, O independent, biocompatible and stable over 2 weeks.